School Readiness in Weekly Iron Folic Acid Supplementation Program in Urban Area, West Java, Indonesia - Apriningsih Apriningsih; Siti Madanijah; Cesilia Meti Dwiriani; Risatianti Kolopaking; Yessi Crosita (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
Background:School based weekly iron and folic acid supplementation (WIFAS) program was aimed to decrease anemia prevalence and improve the adherence to consume iron tablet.Limited information on the school perspective and their readiness to implement the program.Objectives:To analyze program guidelines, stakeholders’ perspective and school readiness to implement the program which will help evaluate and improve adherence to WIFAS.Methods:Using cross sectional design with mixed method approach to utilize social ecological model and community readiness model.Results: Most of schools received awareness campaign regarding the program,only 38,9% have conducted a drinking together session once a week,only 27,8% recorded their students’ adherence.The average score for the school readiness was 3.36 (SD ±0.82), the school was in the vague awareness stage.There is a correlation between the score of school’s knowledge, attitude toward WIFAS program,City Health Authority and Education Regional Office ‘s support score, the total score of the school readiness, ever got socialization with implementation of WIFAS (r= 0.35, r=0.2, r=0.49, r=0.21, r= 0.66, r= 0.43, p value <0.005).The strongest correlation with implementation of WIFAS at school was the school readiness total score, ever received socialization and score school’s knowledge on WIFAS (p value <0.005) and City health Authority and Education regional office’s support score for WIFAS program as covariant (p >0.05).Conclusions: School readiness is important factor of community and environment which contribute to behavior change.School realize that anemia and schoolgirl adherence to consume WIFAS had to solved but did not know how and assume outside parties can help solve the problem.The City Health Authority and Education Regional Office is expected to help improve the school readiness to implement the program.